Associations of HIV testing and late diagnosis at a Japanese university hospital (Clinics, 2016)
OBJECTIVES: This study was conducted to clarify the rate of late diagnosis of HIV infection and to identify relationships between the reasons for HIV testing and a late diagnosis. METHODS: This retrospective cohort study was conducted among HIV-positive patients at the Jikei University Hospital between 2001 and 2014. Patient characteristics from medical records, including age, sex, sexuality, the reason for HIV testing and the number of CD4-positive lymphocytes at HIV diagnosis, were assessed. RESULTS: A total of 459 patients (men, n=437; 95.2%) were included in this study and the median age at HIV diagnosis was 36 years (range, 18-71 years). Late (CD4 cell count